Evaluation of synergy between host and pathogen-directed therapies against intracellular Leishmania donovani. (August 2019) - Zahid, M. Shamim Hasan; Johnson, Monica M.; Tokarski, Robert J.; Satoskar, Abhay R.; Fuchs, James R.; Bachelder, Eric M.; Ainslie, Kristy M.
Abstract: Visceral leishmaniasis (VL) is associated with treatment complications due to the continued growth of resistant parasites toward currently available pathogen-directed therapeutics. To limit the emergence and combat resistant parasites there is a need to develop new anti-leishmanial drugs and alternative treatment approaches, such as host-directed therapeutics (HDTs). Discovery of new anti-leishmanial drugs including HDTs requires suitable in vitro assay systems. Herein, we modified and evaluated a series of resazurin assays against different life-stages of the VL causing parasite, Leishmania donovani to identify novel HDTs. We further analyzed the synergy of combinatorial interactions between traditionally used pathogen-directed drugs and HDTs for clearance of intracellular L. donovani . The inhibitory concentration at 50% (IC50 ) of the five evaluated therapies [amphotericin B (AMB), miltefosine, paromomycin, DNER-4, and AR-12 (OSU-03012)] was determined against promastigotes, extracellular amastigotes, and intracellular amastigotes of L. donovani via a resazurin-based assay and compared to image-based microscopy. Using the resazurin-based assay, all evaluated therapies showed reproducible anti-leishmanial activity against the parasite's different life-stages. These results were consistent to the traditional image-based technique. The gold standard of therapy, AMB, showed the highest potency against intracellular L. donovani, and was further evaluated for combinatorial effects with the HDTs. Among the combinations analyzed, pathogen-directed AMB and host-directed AR-12 showed a synergistic reduction of intracellular L. donovani compared to individual treatments. The modified resazurin assay used in this study demonstrated a useful technique to measure new anti-leishmanial drugs against both intracellular and extracellular parasites. The synergistic interactions between pathogen-directed AMB and host-directed AR-12 showed a great promise to combat VL, with the potential to reduce the emergence of drug-resistant strains. Graphical abstract: Image 1 Highlights: An inexpensive and simple modified resazurin drug screening assay for Leishmania donovani. Anti-leishmanial therapies are evaluated in axenic amastigotes, promastigotes, and intracellular Leishmania donovani. Identification of synergistic, additive, and antagonistic activity between therapies. Amphotericin B and host-directed AR-12 had significant synergistic anti-leishmanial activity.